Human rights accountability for maternal death and failure to provide safe, legal abortion : the significance of two ground-breaking CEDAW decisions - Kismodi, Eszter [et al] (2012)
Examines the issues of women's access to appropriate and quality maternal health services and to safe, legal abortion in the light of two landmark decisions issued in 2011 by the Committee on the Elimination of Discrimination against Women (CEDAW).